2018
DOI: 10.1149/2.0051809jss
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Tribological and Kinetic Attributes of Retaining Rings in Chemical Mechanical Planarization

Abstract: We have successfully applied the Stribeck+ curve to determine the tribological mechanism involved in the ring-slurry-pad interface during CMP at various pressures and velocities. Using two types of slurries (one for copper and another for inter-layer dielectric polishing) and two differently designed rings made of polyether ether ketone (PEEK), one with sharp slots and the other with rounded slots. We find "boundary lubrication" as the initial dominant lubrication mechanism followed by a transition to "mixed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…Poly(aryl ether ketone)s (PAEKs) are a family of high‐performance thermoplastics that offer excellent chemical and thermal resistance, good mechanical properties, and manufacturability into end‐use components for critical applications. They find widespread use in the medical, semiconductor manufacturing, aerospace, automotive and petrochemical industries. Poly(ether ether ketone) (PEEK) (Figure (a)) is the most widely available of the PAEK family, has the largest production volume, and performs well in most sealing and connector applications that involve contact with drilling fluids and sour (sulfur containing) crude oil under high‐pressure and high‐temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(aryl ether ketone)s (PAEKs) are a family of high‐performance thermoplastics that offer excellent chemical and thermal resistance, good mechanical properties, and manufacturability into end‐use components for critical applications. They find widespread use in the medical, semiconductor manufacturing, aerospace, automotive and petrochemical industries. Poly(ether ether ketone) (PEEK) (Figure (a)) is the most widely available of the PAEK family, has the largest production volume, and performs well in most sealing and connector applications that involve contact with drilling fluids and sour (sulfur containing) crude oil under high‐pressure and high‐temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…44 Directivity itself (taken from the science of characterizing old Italian violins, which believe it or not, have many similarities to CMP tools) [45][46][47][48][49][50] is defined as the ratio of measured variances in shear force to variances of normal force at a given polishing PV condition. 44,[51][52][53][54][55] Here, the fluctuating components of shear and normal forces are the key factors and not their absolute values. In this case, the ordinate and the abscissa are independent of one another, and because we use linear scales, there are no distortions or optical illusions that would have been caused by the logarithmic scales.…”
Section: Parametersmentioning
confidence: 99%
“…This is important because a recent study by our team has shown that, for a total of eight retaining rings each made of a different engineered plastic material and processed differently, Δ seems to correlate nicely with the corresponding ring wear rate (RWR). 51 This suggests that, in principle, one can reduce RWR by 4X by simply wearing the ring under conditions corresponding to Step No. 2 of Table II where vibrations ought to also be minimal.…”
Section: Parametersmentioning
confidence: 99%
“…(12)(13)(14)(15)(16)(17) Previous work has focused on the vibrations that occur in various CMP processes. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) Fukuroda et al, Hetherington et al, Kojima et al and Rao et al studied vibrations in CMP and found that they could be used as an end-point detection technique for polishing different materials. (18)(19)(20)(21) However, the authors did not correlate the vibrations to RR.…”
Section: Introductionmentioning
confidence: 99%
“…Of the works that have studied vibrations in CMP, several have focused on Δ's role in the process. (12)(13)(14)(15)(16)(17) Philipossian et al…”
Section: Introductionmentioning
confidence: 99%